Whole-slide imaging in cytopathology: state of the art and future directions. Issue 11 (November 2021) - Marletta, Stefano; Treanor, Darren; Eccher, Albino; Pantanowitz, Liron
Abstract: Whole slide imaging (WSI) has been increasingly adopted for digital evaluation of surgical pathology specimens. Unlike histological slides, cytological preparations frequently display a heterogeneous distribution of cells throughout slides in different focal planes sometimes admixed with obscuring material, therefore requiring multiple scanning planes which significantly lengthens image acquisition and evaluation times. Although examination of digital images can be more advantageous than conventional glass slides, the challenges of focusing, scanning and screening cytological specimens and the associated increase in scan times and data storage needs have limited the routine application of WSI in cytopathology practice. Emerging digital systems designed to overcome image acquisition obstacles coupled with artificial intelligence algorithms augmenting screening of digital cytology slides offer innovative solutions to address these limitations. The aim of this review is to critically address the potential benefits and pitfalls of employing WSI in cytopathology practice and to introduce promising state-of-the-art solutions on the horizon.